Dossier thématique AVENIR : Résilience face au changement climatique - Mwongera, Caroline (2022)
The Adaptation and Valorization of Entrepreneurship in Irrigated Agriculture (AVENIR) project aims to enhance the well-being and resilience of farming households in Senegal, particularly women and youth. The project focuses on smallholder farms that use irrigation and promotes affordable agricultural practices and technologies that can help farming systems become more resilient to a changing climate. This brief outlines the AVENIR approach used to strengthen climate resilience amongst rural farmers of Tambacounda and Sédhiou.